Specyfika leśnictwa regionów Ukrainy - Boiko, Sergii (Leśne Prace Badawcze, 2012)
The distribution of Ukraine’s forests is very uneven: most are concentrated in the Polissya region and in the Carpathians. There are significant differences in the species composition and productivity of stands from different regions which require different approaches to their forest management. Forest cover differs vastly among zones and is not optimal in any of them. The optimal forest cover in Ukraine is considered to be 19% (currently 15.6%) over the whole country, and by region: for the Polissya zone – 32% (currently 26.8%); forest-steppe zone – 18% (currently 13%); steppe zone – 9% (currently 5.3%); Carpathian region – 45% (currently 42%); and the Crimean region – 19% (currently 10.4%). Achieving the optimum forest cover would be possible by afforestation of 2 million hectares of former farmland which is currently wasteland. The existing age structure of forests will not provide stable and sustainable forests, because of dominance by young (32%) and middle age stands (45%). The share of IV and V age classes is only 12% and 11% of the total area respectively (optimal age structure is accordingly 36%, 26%, 19% and 19%). The structure of pine stands is the most unbalanced. The existing age structure and its dynamics indicate that in the future forest use is expected to significantly increase. Forest plantations occupy approximately 50% of the total forest area, and predominate in forest-steppe and steppe zones. The species composition in 14% of the forest plantations is inadequate to provide desirable habitat, and many stands in the steppe zone and Crimean region have very low productivity.